Gender Differences in Hemocyte Immune Parameters of Hong Kong Oyster Crassostrea hongkongensis During Immune Stress - Lu, Jie; Shi, Yanyan; Yao, Tuo; Bai, Changming; Jiang, Jingzhe; Ye, Lingtong (Frontiers in Immunology, 2021)
Gender differences in individual immune responses to external stimuli have been elucidated in many invertebrates. However, it is unclear if gender differences do exist in the Hong Kong oyster Crassostrea hongkongensis, one of the most valuable marine species cultivated along the coast of South China. To clarify this, we stimulated post-spawning adult C. hongkongensis with Vibrio harveyi and lipopolysaccharide (LPS). Gender-based differences in some essential functional parameters of hemocytes were studied via flow cytometry. Obvious gender-, subpopulation-, and immune-specific alterations were found in the hemocyte immune parameters of C. hongkongensis. Three hemocyte subpopulations were identified: granulocytes, semi-granulocytes, and agranulocytes. Granulocytes, the chief phagocytes and major producers of esterase, reactive oxygen species, and nitric oxide, were the main immunocompetent hemocytes. Immune parameter alterations were notable in the accumulation of granulocyte esterase activities, lysosomal masses, nitric oxide levels, and granulocyte numbers in male oysters. These results suggest that post-spawning-phase male oysters possess a more powerful immune response than females. Gender and subpopulation differences in bivalve immune parameters should be considered in the future analysis of immune parameters when studying the impact of pathogenic or environmental factors.